2017
DOI: 10.1088/1748-0221/12/06/c06025
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of laser driven proton beams by an innovative target scheme

Abstract: Proton beams driven by the target normal sheath acceleration mechanism exhibit large divergence and a broad energy distribution with low particle number at high energy. Such undesirable characteristics of the beam can be controlled and optimised by employing a recently developed helical coil technique, which exploits the transient self-charging of solid targets irradiated by intense laser pulses. Highly chromatic focusing of the broadband proton beams was achieved by employing this technique at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 24 publications
0
8
1
Order By: Relevance
“…This current propagates along the helical coil and produces an electromagnetic pulse inside and outside the helical structure, which acts on the proton beam. Contrary to what has been described in the past publications 30,[35][36][37]44,45 , we have demonstrated that the current pulse does not propagate with a constant phase velocity calculated from the coil geometry (1), but that it is dispersed in velocity due to the frequency dependence of the capacitance and inductance of the helical coil. This dispersion modulates the current intensity during its propagation along the helical coil, negative current pulses appear and lead to a favorable configuration of the longitudinal electric field for the proton bunching.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This current propagates along the helical coil and produces an electromagnetic pulse inside and outside the helical structure, which acts on the proton beam. Contrary to what has been described in the past publications 30,[35][36][37]44,45 , we have demonstrated that the current pulse does not propagate with a constant phase velocity calculated from the coil geometry (1), but that it is dispersed in velocity due to the frequency dependence of the capacitance and inductance of the helical coil. This dispersion modulates the current intensity during its propagation along the helical coil, negative current pulses appear and lead to a favorable configuration of the longitudinal electric field for the proton bunching.…”
Section: Discussioncontrasting
confidence: 99%
“…This comparison demonstrates that the helical coil has focused a large number of protons which were not emitted originally in its aperture angle. By considering a short current pulse propagating along the helical wire with the velocity v i ≈ c 30,36 , one may expect that the collimated protons are the ones which propagate with the same velocity as the current pulse along the coil axis:…”
Section: B Experimental Results and Evidence Of Proton Focusing Post-acceleration And Energy Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proton radiography was successfully applied to measure the electromagnetic wave produced by the interaction of a high-intensity laser pulse with solid targets [48,149] . In more recent experiments, this method was applied for studies of the return current propagating in a wire connecting the target to the ground [49,68,[150][151][152] . Figure 52(a) shows a setup for the investigation of the EMP propagating along a folded meander wire [49,68,150,151] .…”
Section: Charged Particle Deflection For Electromagnetic Field Probingmentioning
confidence: 99%
“…In more recent experiments, this method was applied for studies of the return current propagating in a wire connecting the target to the ground [49,68,[150][151][152] . Figure 52(a) shows a setup for the investigation of the EMP propagating along a folded meander wire [49,68,150,151] . The main laser beam ejects electrons and generates a positive charge on the target, inducing a pulse of return current propagating along the wire to the ground.…”
Section: Charged Particle Deflection For Electromagnetic Field Probingmentioning
confidence: 99%